Comparative study of 1,2-dimethylhydrazine and azoxymethane on the induction of colorectal cancer in rats - Jucá,Mario Jorge (2014)
The induced colorectal carcinogenesis in rodents has a long history and currently uses the substances 1,2-dimethylhydrazine and azoxymethane. Objective: The aim of this study was to compare the inductive effect of the substances azoxymethane and 1,2-dimethylhydrazine in colorectal carcinogenesis. Method: 30 randomly chosen male Wistar rats were divided into four groups. G1 group was treated with 1,2-dimethylhydrazine and C1 was its control group; G2 group was treated azoxymethane and C2 was its control group. The animals were weekly weighed until euthanasia, when their intestines were removed, processed and analyzed by an experienced pathologist. Results: Among the control groups (C1 and C2) no histologic changes were observed; moderate dysplasia was detected in G2 group; hyperplasia, mild dysplasia, severe dysplasia and carcinoma were observed in G1 group. When this study compared the cost of the substances, 1,2-dimethylhydrazine was more than 50 times less expensive than azoxymethane. Conclusion: Azoxymethane is able to promote histological changes consistent with colorectal carcinogenesis. 1,2-Dimethylhydrazine produced neoplasia and dysplasia, and, compared to the azoxymethane, was more efficient in the induction of colorectal cancer.